Hollow and Concave Nanoparticles via Preferential Oxidation of the Core in Colloidal Core/Shell Nanocrystals - Miszta, Karol (American Chemical Society, 2014)
[Image: see text] Hollow and concave nanocrystals find applications in many fields, and their fabrication can follow different possible mechanisms. We report a new route to these nanostructures that exploits the oxidation of Cu(2–x)Se/Cu(2–x)S core/shell nanocrystals with various etchants. Even though the Cu(2–x)Se core is encased in a thick Cu(2–x)S shell, the initial effect of oxidation is the creation of a void in the core. This is rationalized in terms of diffusion of Cu(+) ions and electrons from the core to the shell (and from there to the solution). Differently from the classical Kirkendall effect, which entails an imbalance between in-diffusion and out-diffusion of two different species across an interface, the present mechanism can be considered as a limiting case of such effect and is triggered by the stronger tendency of Cu(2–x)Se over Cu(2–x)S toward oxidation and by fast Cu(+) diffusion in copper chalcogenides. As the oxidation progresses, expansion of the inner void erodes the entire Cu(2–x)Se core, accompanied by etching and partial collapse of the shell, yielding Cu(2–x)S(y)Se(1–y) concave particles.